Exploring undergraduate experiences in physical education and health: A photovoice study of Indonesian students - Basuki, Sunarno; Perdinanto, Perdinanto; Amirudin, Akhmad (Indonesian Journal of Research in Physical Education, Sport, and Health, 2025)
Background: Research on undergraduate students in Physical Education (PE) and Health particularly in Indonesia and the Global South has predominantly relied on quantitative indicators, often neglecting students’ lived, embodied, and emotional experiences within demanding academic and physical environments. Objective: This study aimed to explore the lived experiences of Indonesian undergraduate students enrolled in PE and Health programs and to examine how these experiences can inform more responsive and inclusive educational practices. Methods: A qualitative participatory design was employed using photovoice. Eight undergraduate students documented their academic and personal experiences through photography over a two-week period, followed by reflective writing and focus group discussions. Data were analyzed thematically through collaborative coding, guided by experiential learning principles. Result: Three central themes emerged. First, Balancing Academic and Physical Demands revealed a dual burden of physical exhaustion and academic discipline. Second, Identity, Belonging, and Community highlighted the vital role of peer, family, and social support in sustaining motivation and resilience. Third, Navigating Uncertainty and Emotional Pressure reflected students’ anxieties related to career prospects, professional readiness, and structural constraints within the field of physical education. Conclusion: The findings demonstrate that photovoice effectively captures nuanced student experiences often overlooked by conventional approaches, while simultaneously fostering reflection and empowerment. Engaging students as co-constructors of knowledge offers valuable insights for developing more student-centered, supportive, and inclusive learning environments in Physical Education and Health programs.